1997
DOI: 10.1095/biolreprod57.6.1328
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Serum Follicle-Stimulating Hormone Concentrations Alters Key Intrafollicular Growth Factors Involved in Selection of the Dominant Follicle in Heifers1

Abstract: Declining FSH after a transient rise coincides with selection of a dominant follicle (DF) and atresia of the remaining cohort follicles (subordinates) in cattle. The objectives of this study were to determine 1) whether intrafollicular amounts of inhibins, activin-A, insulin-like growth factor I (IGF-I), and IGF-I-binding proteins (IGFBP) are altered during selection of the first-wave dominant follicle (DF1) and 2) whether these biochemical markers are FSH dependent. Beef heifers received six or eight 6-h inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
3
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 45 publications
12
92
3
5
Order By: Relevance
“…This conclusion is based on the previously described timing of growth of the first follicle wave of the oestrous cycle, intrafollicular hormone concentrations and the fact that, while morphologically unselected and still FSH 'dependent', the most oestrogenic cohort follicle 1-2 days after wave emergence will most likely become the DF (Mihm et al 1997, Austin et al 2001. Growth characteristics and differences in diameter, steroid concentrations and oestrogenic activity established in this study showed the higher differentiation state of the DF recovered at or shortly after the onset of dominance in accordance with previous characterisations of selected DFs (Ginther et al 2003, Mihm & Bleach 2003.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This conclusion is based on the previously described timing of growth of the first follicle wave of the oestrous cycle, intrafollicular hormone concentrations and the fact that, while morphologically unselected and still FSH 'dependent', the most oestrogenic cohort follicle 1-2 days after wave emergence will most likely become the DF (Mihm et al 1997, Austin et al 2001. Growth characteristics and differences in diameter, steroid concentrations and oestrogenic activity established in this study showed the higher differentiation state of the DF recovered at or shortly after the onset of dominance in accordance with previous characterisations of selected DFs (Ginther et al 2003, Mihm & Bleach 2003.…”
Section: Discussionmentioning
confidence: 99%
“…These two transcripts encoded a novel 3 0 truncated aromatase variant (deposited under NCBI accession number DQ004742 and recently matched to Bt.4447), and an untranslated mRNA sequence recently matched to the UniGene cluster Bt.33875 (deposited under NCBI accession number AY999166). In addition, SAGE analysis of transcripts upregulated in the DF granulosa cells confirmed four known genes encoding cytochrome P450 aromatase (CYP19A1), glutathione S-transferase A2 (GSTA2), inhibin a-subunit (INHA) and glia-derived nexin (SERPINE2), which regulate follicular E synthesis, antioxidant activity and extracellular tissue remodelling in the selected DF (Mihm et al 1997, Sisco et al 2003, Evans et al 2004, Fayad et al 2004.…”
Section: Sage Analysis Of Differentially Expressed Transcripts In Thementioning
confidence: 93%
See 1 more Smart Citation
“…Results of many studies are compatible with a role for the IGF system in deviation but seem at least partly equivocal, owing to one or more of the following: (1) the reference point was not readily related to the beginning of deviation (Mihm et al 1997, Spicer et al 2005; (2) a differential change between LF and second LF began at the equivalent of the beginning of deviation, rather than before the beginning of deviation (Beg et al 2001, Ginther et al 2003b or (3) total IGF-I rather than free IGF-I was considered (De la Sota et al 1996, Mihm et al 1997. In cattle, the concentrations of free IGF-I did not increase in the LF in association with deviation, but began to decrease in the second LF before the beginning of deviation (Figs 2 and 3, Beg et al 2002).…”
Section: Igf Systemmentioning
confidence: 99%
“…In conclusion, the decline in FSH beginning after Day 2 of the heifer oestrous cycle causes differential alterations in FSH dependent growth factors and hormones within the cohort of preselection follicles, simultaneously inducing growth and enhanced estradiol producing capacity of the DF and atresia of subordinate follicles (MIHM et al, 1997).…”
Section: Recruitmentmentioning
confidence: 93%